Pengembangan Instrumen Penilaian Afektif (Attitude Toward Physics) Dengan Teknik Peer And Self Assessment Untuk Menumbuhkan Sikap Tanggung Jawab Dan Kerjasama Peserta Didik SMA - Lia Wahyuningsih Budiarti; Edi Istiyono (Postgraduate, University of Mataram, 2023)
This study aims to develop an assessment instrument (Attitude Toward Physics) with Peer and Self Assessment Techniques to Grow an Attitude of Responsibility and Student Cooperation towards learning physics. The research method used is development research. The research design is in the form of a 4-D model developed by Thiagarajan (1994) with stages that include define, design, develop, and dissemination. Test the validity of the instrument using content validation carried out by the validator. Analysis of the reliability of the instrument using the Alpha Crounbach formula. The validation results from the validator state that the affective assessment instrument (Attitude Toward Physics) with Peer and Self Assessment Techniques to Grow Students' Attitudes of Responsibility and Cooperation towards learning physics is feasible to use.